A new approach in the synthesis of La1−xGdxFeO3 perovskite nanoparticles – structural and magnetic characterization. Issue 46 (3rd November 2015) - Wiglusz, R. J.; Kordek, K.; Małecka, M.; Ciupa, A.; Ptak, M.; Pazik, R.; Pohl, P.; Kaczorowski, D.
Abstract : A series of highly crystalline orthoferrite nanoparticles (type La1− x Gd x FeO3, where x = 0 to 1) were prepared using the self-combustion method. Abstract : A series of highly crystalline orthoferrite nanoparticles (type La1− x Gd x FeO3, where x = 0 to 1) were prepared using the self-combustion method. Extensive studies including X-ray diffraction, Rietveld refinement and Fourier transform infrared spectroscopy as well as Raman spectroscopy confirmed the orthorhombic space group Pnma of the obtained materials. The calculated average grain size for powders is in the range of 30 to 80 nm. Magnetic characterization of the La1− x Gd x FeO3 series, performed at 1.72 K, indicated an antiferromagnetic state characterized by some canting of iron magnetic moments, in good agreement with the data reported for similar fine-particle systems.